Studi Implementasi Manajemen Risiko di PT. Lippo General Insurance Tbk. Selama Periode 2022-2024 - Iswardhani, Indri (Manajemen Kreatif Jurnal, 2025)
This study analyzes the implementation of risk management at PT Lippo General Insurance Tbk over 2022–2024 using a qualitative descriptive approach. The review focuses on the four core risk-management cycles: identification, measurement, monitoring, and mapping–mitigation and on one key output: the risk profile assessment (inherent risk rating, quality rating of risk-management implementation, and implementation of risk level). The results indicate that risk-management processes are consistent and well documented through a risk register and supported by a Risk Management Information System, enabling rapid linkage of findings to action plans. Overall, the composite risk profile remains low, underpinned by a moderately strong quality of implementation and risk-level application. On the inherent-risk dimension, dynamics are observed: strategic risk improves in the final year, while insurance, credit, and liquidity risks rise relative to 2023. Nevertheless, the consistency of implementation quality and disciplined execution mitigates these effects, keeping the composite profile stable. Managerial implications include strengthening underwriting and claims management, enhancing counterparty and reinsurance quality, and enforcing liquidity discipline, while maintaining a strong risk culture and tiered monitoring mechanisms.